Rekrutmen Dan Kaderisasi Calon Legislatif Perempuan Pada Pemilihan Umum 2019 Oleh Partai Keadilan Sejahtera - Melna Andani; Ridhah Taqwa; Zulfikri Suleman (Universitas Muhammadiyah Tapanuli Selatan, 2019)
The purpose of this study was to analyze how the regeneration of female legislative candidates in the 2019 general electionby the Keadilan Sejahtera Party Ogan Komering Ilir Regency. By using qualitative verification, The interview was conducted from informants who were women legislative candidates and the management structure in the Keadilan Sejahtera Party of Ogan Komering Ilir Regency, The results of this study is Keadilan Sejahtera Party conducted a member recruitment process using a selection mechanism, namely (1). PKS through PKS through Rohis, mosque youth association, campus missionary organization, youth organization and community in branch management council (2) screening every beginner member in accordance with the specified conditions. (3). Determination as a member. PKS also recruits female legislative candidates with several channels, namely (1). Based on the capabilities and expertise possessed by internal and external members such as social, political and economic capital. (2) based on regeneration, members who are at the level of young members who can become candidates.